Nieortodoksyjny aspekt obrazu Soni Marmieładowej - Czapp, Krystyna (Przegląd Rusycystyczny, 2012)
Krystyna Czapp Uniwersytet Gdański, Gdańsk, Poland prz.rus@op.pl НЕОРТОДОКСАЛЬНЫЙ АСПЕКТ ОБРАЗА СОНИ МАРМЕЛАДОВОЙ Резюме Целью статьи является попытка показать влияние некоторых протестантских доктрин на образ героини Преступления и наказания федора Достоевского Сони Мармеладовой. Возможно, что на русского писателя могло повлиять так называемое «евангельское пробуждение» — движение по своей сути протестантское, которое началось в России в конце 50-х годов XIX века. Многие россиане приняли тогда протестантизм. Слова Библии ввел Достоевский в художественный мир Преступления и наказания именно через образ Сони Мармеладовой. В предлагаемой статье экспонируется факт, что единственным источником надежды для Сони были слова евангелия, каторое она читала дома и прочла Раскольникову, веря, что это приведет его к обращению к Богу. личное отношение к Новому завету приближает Соню Мармеладову к протестант-ской традиции, где не существует разделения на священнослужителей и прихожан, а ежедневное чтение Библии является чуть ли не обязанностью. THE UNORTHODOX ASPECT OF THE FIGURE OF SONYA MARMELADOVA Summary The aim of the article is to demonstrate the impact of the Protestant doctrine on Sonya Marmeladova — a heroine of Crime and Punishment by Fyodor Dostoyevsky.It is possible that the Russian writer could be influenced by the Evangelical Awakening — a Protestant in its essence movement that had its beginning in Russia at the end of 50s of the 19th century. There were many Russians converted to Protestantism at that time.The words of the Bible introduced by Dostoyevsky in the artistic world of Crime and Punishment are through the character of Sonya Marmeladova. This article exposes the fact Еhat the only sources of hope for Sonya were the words of the Gospel, which she wrote herself in her home and read Raskolnikov in faith that the words of the New Testament would lead him to repentance to God. Sonya by reading the Gospel for Raskolnikov, took the role of a shepherd of souls. This personal approach to the Gospel gets Sonya Marmeladova closer to the Protestant tradition, where there is no distinction berween clergy and laity, and the daily reading of the Bible is almost an obligation.